Pelatihan Diversivikasi Produk Olahan Ikan Lele Sebagai Alternatif Usaha untuk Meningkatkan Pendapatan di Kecamatan Koto Tangah Kota Padang - Imtihan Imtihan; Lisa Mayasari; Yulhendri Yulhendri; Fikra Fikra; Dahnil Mar. J (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The Koto Tangah Subdistrict, Padang  is the location for implementing community service program activities in order to increase the income of catfish cultivators in the Koto Tangah Subdistrict, Padang. The partner of this Commuonity Service Program is a catfish farming group led by Cv.Family Pisces. The local community has carried out a catfish farming business but in its development faced several obstacles such as the low selling price of catfish. The solution to overcome these problems is through diversification of catfish products into processed fish that have added value to produce higher selling points and profit levels. So that it has an impact on increasing the income of catfish cultivators in the Koto Tangah sub-district, Padang. The implementation of this program was carried out using a participatory method through socialization, counseling and training activities. The processed catfish products produced are in the form of fresh catfish, catfish nuggets and catfish meatballs. The results of the business analysis show that with fresh catfish production of 50 kg/month and selling price of Rp. 80,000/kg, the income is Rp.4,000,000/month.The production of catfish meatballs of 20 kg/month with a selling price of Rp. 80,000/kg generates an income of Rp. 1.600.000/month. Furthermore, the production of catfish nuggets of 20 kg/month with a selling price of Rp. 100,000/kg generates an income of Rp. 2,000,000/month.